Construction of Family Company Sustainability Model Based on Corporate Sustainability Theory (Case Study of Family Companies In Semarang And Surroundings) - Sulistiono, Arie; Widianarko, Budi; Retnowati , Berta Bekti (Eduvest - Journal of Universal Studies, 2023)
Every Company or corporation is expected to have sustainability in its business, including family companies which are the largest part of the Company's ranks. Corporate sustainability theory is one of the filters and, simultaneously, the inspiration for companies to survive or not on their journey. This study uses qualitative research methods as a knife to dissect various facts and facts about the family business. With a systematic data collection process, data validation by triangulation, and data processing to the conclusion of research data based on the relationship between the revealed propositions. Furthermore, by utilizing applicative software that helps find the main topics discussed among family business practitioners from the interviews conducted, it contributes to understanding the family company Sustainability model in a review of the theory of corporate sustainability. The results of this study will present a conclusion based on accurate and relevant data to answer the research question of how to build the sustainability of a family company and produce a construction of a family company sustainability model based on the theory of corporate sustainability.